Development and Physicochemical Evaluation of a Polyherbal Dual-Action Shampoo for Hair Coloring and Conditioning: Research Article (Journal of Pharma Insights and Research, 2025)
The cosmetic formulations have witnessed a paradigm shift towards natural molecules, driven by raising concerns regarding the dermatological and systemic toxicity associated with synthetic hair dyes and surfactants. Conventional hair coloring systems, frequently laden with para-phenylenediamine (PPD) and ammonia, are implicated in contact dermatitis, cytotoxicity, and structural damage to the hair keratin. This study explains about the formulation and evaluation of a novel polyherbal shampoo designed to function synergistically as a natural hair colorant and a conditioner, thereby eliminating the need for multi-step hair care regimens. The formulation incorporates Lawsonia inermis and Indigofera tinctoria as primary chromophores, augmented by the anthocyanins of Hibiscus rosa-sinensis, while conditioning is achieved through the bioactive mucilage and phytosterols of Aloe barbadensis, Eclipta alba, and Trigonella foenum-graecum. Physicochemical characterization revealed that the optimized formulation possesses a slightly acidic pH compatible with the scalp’s acid mantle, alongside appropriate rheological properties ensuring ease of application and spreadability. Spectrophotometric analysis confirmed the effective deposition of lawsone and indigotin on hair shafts, offering a safe spectrum of brown to black hues tailored by the ratio of botanical dyes. Moreover, the inclusion of saponin-rich botanicals facilitated adequate foaming and cleansing action without stripping natural oils. Accelerated stability studies indicated that the formulation maintains its organoleptic and physicochemical integrity over a thirty-day storage period. These results suggest that the developed herbal shampoo offers a viable, non-toxic alternative to synthetic counterparts, effectively combining aesthetic coloring with therapeutic hair care